Some New Observations on Wijsman ℐ2-Lacunary Statistical Convergence of Double Set Sequences in Intuitionistic Fuzzy Metric Spaces - Ömer Kişi (Journal of Mathematics)
In this study, we investigate the notions of the Wijsman ℐ2-statistical convergence, Wijsman ℐ2-lacunary statistical convergence, Wijsman strongly ℐ2-lacunary convergence, and Wijsman strongly ℐ2-Cesàro convergence of double sequence of sets in the intuitionistic fuzzy metric spaces (briefly, IFMS). Also, we give the notions of Wijsman strongly ℐ2∗-lacunary convergence, Wijsman strongly ℐ2-lacunary Cauchy, and Wijsman strongly ℐ2∗-lacunary Cauchy set sequence in IFMS and establish noteworthy results.